Comparative Intradermal Tuberculin Testing of Free-Ranging African Buffaloes (Syncerus caffer) Captured for Ex Situ Conservation in the Kafue Basin Ecosystem in Zambia - Hetron Mweemba Munang'andu; Victor Siamudaala; Wigganson Matandiko; Andrew Nambota; John Bwalya Muma; Aaron Simanyengwe Mweene; Musso Munyeme (Veterinary Medicine International)
Bovine tuberculosis (BTB) is endemic in African buffaloes (Syncerus caffer) in some National Parks in Southern Africa, whilst no studies have been conducted on BTB on buffalo populations in Zambia. The increased demand for ecotourism and conservation of the African buffalo on private owned game ranches has prompted the Zambian Wildlife Authority (ZAWA) and private sector in Zambia to generate a herd of “BTB-free buffaloes” for ex situ conservation. In the present study, 86 African buffaloes from four different herds comprising a total of 530 animals were investigated for the presence of BTB for the purpose of generating “BTB free” buffalo for ex-situ conservation. Using the comparative intradermal tuberculin test (CIDT) the BTB status at both individual animal and herd level was estimated to be 0.0% by the CIDT technique. Compared to Avian reactors only, a prevalence of 5.8% was determined whilst for Bovine-only reactors a prevalence of 0.0% was determined. These results suggest the likelihood of buffalo herds in the Kafue National Park being free of BTB.